Genomic characterization and phylogenetic analysis of SARS‐COV‐2 in Italy. Issue 9 (10th April 2020) - Zehender, Gianguglielmo; Lai, Alessia; Bergna, Annalisa; Meroni, Luca; Riva, Agostino; Balotta, Claudia; Tarkowski, Maciej; Gabrieli, Arianna; Bernacchia, Dario; Rusconi, Stefano; Rizzardini, Giuliano; Antinori, Spinello; et al.
Abstract: This report describes the isolation, molecular characterization, and phylogenetic analysis of the first three complete genomes of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) isolated from three patients involved in the first outbreak of COVID‐19 in Lombardy, Italy. Early molecular epidemiological tracing suggests that SARS‐CoV‐2 was present in Italy weeks before the first reported cases of infection.